ANALYSIS OF WASTE IN THE HEMODIALYSIS SERVICE CLAIM PROCESS AT UNIVERSITAS MUHAMMADIYAH MALANG GENERAL HOSPITAL - Amalia Rizki, Nurul; Rusca Putra, Kuswantoro; Syamsiah anwar, Jamilatus (Universitas Brawijaya, 2025)
Hospitals as healthcare providers depend on the claims process to maintain financial stability, especially in the National Health Insurance (JKN) program managed by BPJS. Inefficient claims management can cause delays in fund disbursement and increase pending claims. This descriptive qualitative study identifies waste in the Hemodialysis (HD) service claim process at RSU UMM using the Lean Management approach. The results of the analysis showed that administrative defects were the biggest waste with 22 occurrences, caused by paper-based manual systems, such as duplication or loss of files. In addition, waiting time waste was found 14 times, as well as overprocessing and motion 3 times each. To improve efficiency, digitization of the claims system is recommended to reduce administrative errors and speed up the disbursement process